INCIDENCE OF INFECTIONS DURING THE APPLICATION OF HIGH-DOSE CHEMOTHERAPY WITH AUTOLOGOUS STEM CELL TRANSPLANTATION - Milosević, Milica; Bila, Jelena; Stanisavljevic, Dejana; Todorovic Balint, Milena (Srpski medicinski časopis Lekarske komore, 2021)
Introduction: Autologous stem cell transplantation (AHSCT) is a well-established therapy for hematologic malignancies. Changes in transplantation strategies and improvement in supportive care have significantly altered the incidence and pattern of infections in these patients.Aim: Evaluating the frequency of infections in the first 30 days after AHSCT, as well as the possible influence of the number of CD34 + stem cells in the graft and of the engraftment parameters: ALC500_20 (absolute lymphocyte count 0.5x109 / L per day + 20), ANC500_11 (absolute neutrophil count 0.5x109 / L per day + 11),and PLT20_13 (platelets 20x109 / L per day + 13), on the occurrence of infections.Materials and methods: The retrospective cohort study examined 80 patients above the age of 20 years, diagnosed with multiple myeloma (MM), non-Hodgkin's (NHL) or Hodgkin's lymphoma (HL), treated at the Clinic for Hematology of the Clinical Center of Serbia, in the period between July 2006 and December 2017. All episodes of fever and/or documented infection during neutropenia have been reported.Results: The average survival after AHSCT was 34.5 months. A total of 54 patients (67.5%) had a documented infection. Gram-positive infections were five times more common than gram-negative. In gram-positive isolates, coagulase-negative staphylococcus – CoNS was the most common (37.0%) pathogen, followed byStreptococcus α haemolyticus (12.4%). Among gram-negative isolates, Escherichia coli was present in 62.5% of the cases, while Klebsiella spp. and Ralstonia pickettii were represented with an equal frequency of 12.5%. Fungal infections were rare (Candida spp., 10.0%). Viral infections were verified in 5 (6.3%) patients (Herpeszoster virus 3.8% and H1N1 2.5%).Conclusion: The number of CD34+ stem cells in the graft, as well as the rate of hematopoietic reconstitution, i.e., the achievement of ALC500_20, ANC500_11, and PLT20_13, were not statistically significant for the development of infections in the early phase after AHSCT.
Keywords: autologous stem cell transplantation; lymphoma; multiple myeloma; infection